Stakeholder-government collaboration in developing cost-effective fishery-independent surveys in rights-based and co-managed fisheries. (June 2021) - Caputi, Nick; de Lestang, Simon; Newman, Stephen J.; Jackson, Gary; Smith, Kim
Abstract: Fishing rights and co-management are considered important aspects of fisheries management. But with rights comes a responsibility to contribute data that improves stock assessments and harvest strategies. This responsibility should include contributing data based on fishery-independent surveys (FIS) that provide robust measures of stock abundance and greater confidence in stock assessments, reducing risks to stock sustainability and resulting in more reliable management. FIS conducted with stakeholders provides a direct link between stock abundance indices and their own experience giving them ownership and a better appreciation of stock status. We examine case studies from Western Australian fisheries in four categories: FIS conducted using research vessels; FIS conducted on recreational fisheries using citizen-science; FIS conducted using volunteer industry vessels, and FIS using chartered industry vessels. These FIS cover fisheries with different gear, management, fishing sectors, value and number of participants. The case studies demonstrate that there are a number of ways that FIS designs may be implemented, with each fishery having a unique approach with a common element that they represent standardised surveys. We consider that all fisheries require some type of FIS and this paper discusses options of how this might be achieved. However, FIS can be expensive, so surveys must be cost effective to ensure that they endure. The approach to developing FIS should include collaboration with stakeholders in a co-management agreement. The FIS could be a requirement of having fishing rights and taken into account when developing management arrangements, e.g. allocation of part of the entitlements for a FIS. Highlights: Fishers with fishing rights and co-management should support stock surveys. Survey designs will vary depending on the objectives and fishery characteristics. Case studies examine surveys with different gear, management, sectors and value. Fishery-independent surveys must be cost effective to ensure that they endure. Survey development should be part of co-management and management arrangements.